Undoing borders and breaking barriers: cartographic representation in contemporary art - Couto, Maria de Fátima Morethy (PORTO ARTE: Revista de Artes Visuais, 2019)
Abstract My presentation aims to analyze the work of contemporary artists who resorted to maps in order to transgress conventional representations, question their neutrality and discuss the place attributed to peripheral countries in the international concert of nations. I will thus emphasize the potential for seemingly banal poetic interventions, but of strong reflective appeal because they misrepresent conventions and representations that are taken as natural. Resumo Minha apresentação tem por objetivo analisar o trabalho de artistas contemporâneos que recorreram a mapas com o intuito de transgredir representações convencionais, questionar sua neutralidade e discutir o lugar atribuído aos países considerados periféricos no concerto internacional de nações. Ressaltarei, assim, o potencial de intervenções poéticas aparentemente banais, mas de forte carga reflexiva pois desconfiguram convenções e representações que são tomadas como naturais.